Frameworks for a computational Isnad authentication and mechanism development - Ibrahim, Nuzulha Khilwani; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Ahmed Ali, Ahmed El-Mogtaba Bannga; Kartiwi, Mira (IEEE, 2016)
These days, there are an increasing number of studies in ICT has been done on the hadith domain in different levels of knowledge of hadith, where a number of studies have been conducted in IT to validate the Ahadith where most of them are based on the matching of test Ahadith with the authentic Ahadith in the database. However, there are limited computerized-based studies to authenticate the ahadith based on scholars’ principles. The three objectives of this study are (1) the principles and specific criteria of the theoretical authentication of isnad al-hadith, (2) a new mechanism of authentication to be applied onto the criteria and (3) a validation phase including user acceptance test (UAT) and domain expert evaluation. Firstly, we need to identify the principles of isnad al-hadith authentication theoretically, which the specific criteria will be proposed based on previous studies and knowledge of hadith. Secondly, a new mechanism will be developed to achieve the authentication of the new criteria of the isnad al-hadith. This mechanism development includes the integration between Islamic knowledge and Information Technology (IT) which we proposed to develop an algorithm based on existing framework with a new elements of fact probing from Islamic knowledge.The accuracy of the authentication process on the domain of knowledge of hadith will be evaluated by domain experts through an interview.